2020
DOI: 10.1002/mbo3.1113
|View full text |Cite
|
Sign up to set email alerts
|

In vitro reconstitution and characterization of pyruvate dehydrogenase and 2‐oxoglutarate dehydrogenase hybrid complex from Corynebacterium glutamicum

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
(103 reference statements)
1
4
0
Order By: Relevance
“…The coexistence of ThDP-dependent dehydrogenase and succinyltransferase domains on the same polypeptide, and their interactions, has obvious implications not only in terms of substrate channelling and catalytic efficiency, but also in terms of regulation, as first suggested by our previous studies on mycobacterial KGD 18 . Furthermore, here we show how the succinyltransferase domain makes use of the same C-terminal structural motif we previously identified in corynebacterial AceF, and adds to the hypothesis of a link between the presence of an OdhA-like, ‘all-in-one’ enzyme and a mixed PDH/ODH supercomplex, which presence, initially proposed on the basis of copurification experiments in C. glutamicum 17 , has been supported by increasing experimental evidence 16,18,35 . It is therefore tempting to speculate that the correlation between the presence of an OdhA-like enzyme bearing both E2o and E1o activities, and a reduced E2p core may be related to the size and hexameric architecture of OdhA, possibly incompatible with its interaction with a canonical cubic or dodecahedral PDH core.…”
Section: Discussionsupporting
confidence: 84%
“…The coexistence of ThDP-dependent dehydrogenase and succinyltransferase domains on the same polypeptide, and their interactions, has obvious implications not only in terms of substrate channelling and catalytic efficiency, but also in terms of regulation, as first suggested by our previous studies on mycobacterial KGD 18 . Furthermore, here we show how the succinyltransferase domain makes use of the same C-terminal structural motif we previously identified in corynebacterial AceF, and adds to the hypothesis of a link between the presence of an OdhA-like, ‘all-in-one’ enzyme and a mixed PDH/ODH supercomplex, which presence, initially proposed on the basis of copurification experiments in C. glutamicum 17 , has been supported by increasing experimental evidence 16,18,35 . It is therefore tempting to speculate that the correlation between the presence of an OdhA-like enzyme bearing both E2o and E1o activities, and a reduced E2p core may be related to the size and hexameric architecture of OdhA, possibly incompatible with its interaction with a canonical cubic or dodecahedral PDH core.…”
Section: Discussionsupporting
confidence: 84%
“…These substrates were chosen as their oxidation is linked to different numbers of NADH-forming reactions. Glucose oxidation to 6 CO 2 involves three NADH-forming reactions [glyceraldehyde 3-phosphate dehydrogenase, pyruvate dehydrogenase complex, and unusual 2-oxoglutarate dehydrogenase complex (Niebisch et al, 2006 ; Hoffelder et al, 2010 ; Bruch et al, 2020 ; Kinugawa et al, 2020 )] and is coupled to the formation of 6 NADH, 2 NADPH, and 4 MQH 2 if the oxidative pentose phosphate pathway is neglected. l -Lactate oxidation to 3 CO 2 involves two NADH-forming reactions (pyruvate dehydrogenase complex, and 2-oxoglutarate dehydrogenase complex) and leads to the formation of 2 NADH, 1 NADPH, and 3 MQH 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent studies confirmed that the succinyl transferase domain of E1oE2o uses the lipoyl groups of E2p to transfer the succinyl group to CoA ( 15 ). Evidence for a hybrid PDH-ODH complex in C. glutamicum was also obtained in a recent biochemical study ( 16 ). Another unusual structural feature was unraveled for the E2p subunit AceF of C. glutamicum ( 17 ).…”
Section: Introductionmentioning
confidence: 55%
“…In actinobacteria, E2p (AceF) also forms a trimer, but a phenylalanine-containing three-residue-insertion in the C-terminal helix prevents higher order oligomerization ( 17 ). Biochemical studies with reconstituted complexes suggested that two AceF trimers form the core of the hybrid complex and are stably associated with Lpd dimers binding to the PSBD domains of AceF ( 16 , 49 ). OdhA was proposed to form hexamers and a smaller oligomer that readily associated with the AceF-Lpd subcomplex, whereas AceE appeared to have a lower affinity for this subcomplex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation